"Epistemic injustice" in the administration of mental health legislation. Issue 1 (2nd January 2021) - Todd, Tom
ABSTRACT: The concept of "Epistemic Injustice" was used as a tool to interpret practices applied during the administration of Mental Health legislation by the Mental Health Tribunal Scotland. This highlighted instances of being wronged on several occasions in my capacity as a knower. Example contributory factors included the Tribunal structure and sub-optimal application of heuristics by panel members. Factors associated with an appeal process involving a "Designated Medical Practitioner" may offer some potential for improvement of routine application of administrative aspects of Mental Health legislation. Testimonial and hermeneutical issues should be considered.